Advances in Systemic Therapy for Advanced Hepatocellular Carcinoma: Paradigm Evolution from Single-Agent Chemotherapy to Targeted Therapy Combined with Immunotherapy - Zhao, Chang (Exploring Science Academic Conference Series, 2026)
Primary liver cancer, particularly hepatocellular carcinoma (HCC), represents a significant global public health burden with persistently high incidence and mortality rates. The systemic treatment of advanced HCC has undergone a paradigm evolution from traditional cytotoxic chemotherapy to molecular targeted therapy, and now to the current era centered on the combination of targeted therapy and immunotherapy. Traditional chemotherapy has shown limited efficacy due to tumor insensitivity and substantial toxicity. Since the approval of sorafenib in 2007, the era of targeted therapy began; however, the efficacy of single -agent targeted therapy has encountered bottlenecks. In recent years, the introduction of immune checkpoint inhibitors has brought breakthroughs. Notably, the “targeted plus immunotherapy” regimen represented by atezolizumab combined with bevacizumab (IMbrave150 study) and the “dual immunotherapy” regimen represented by durvalumab combined with tremelimumab (HIMALAYA study) have been established as new first -line standards for advanced HCC. These approaches have significantly improved objective response rates and overall survival in patients and have been recommended as the highest -level evidence in major clinical guidelines. This article systematically reviews the developmental trajectory of systemic therapy for HCC, comparatively analyzes the efficacy, safety, and applicable populations of key drugs across different eras, and discusses the current challenges facing combination strategies, including drug resistance and biomarker screening. The conclusion highlights that the transition from monotherapy to combination therapy marks the entry of HCC treatment into a new stage characterized by synergistic enhancement, diversified regimens, and a commitment to improving patient prognosis. Future directions will focus on overcoming drug resistance, exploring novel drug combinations (such as antibody -drug conjugates), and achieving more precise individualized treatment through biomarkers.